Verbal direction of internal attention in visual working memory elicits a retro-cue benefit without hemispheric asymmetry in occipital alpha : a MEG study - Virtaintorppa, Teemu (2023)
Visual attention can be focused not only on external stimuli, but also on internal visual working memory (VWM) representations. This internal attention is needed to prioritize relevant over irrelevant memory items, as the capacity of VWM is strictly capacity limited. Previous research has indicated that directing internal attention to VWM representations, as measured by retro-cuing, enhances memory performance. However, the neural mechanisms of this retro-cue benefit are not clear, although the neural marker of hemispheric asymmetry in occipital alpha has been associated with it. Previous research has focused mainly on symbolic cues. In contrast, this thesis investigated the impact of using verbal cues in shifting internal attention to VWM representations on memory performance and alpha activity. Specifically, we aimed to determine whether verbal cues elicit hemispheric asymmetry in occipital alpha and improve memory performance. We also sought to eliminate a confounding variable in the retro-cue paradigm. 14 participants performed a retro-cue task while undergoing MEG. We hypothesized that hemispheric asymmetry in occipital alpha would manifest as decreased alpha activity contralateral to the relevant memory item. We assumed this to be accompanied by a retro-cue benefit. Interestingly, only the latter hypothesis was supported; a clear retro-cue benefit was found, but no statistically significant asymmetry in occipital alpha was evident. We did note a trend towards stronger alpha activity in the right occipital hemisphere. These findings might have been caused by the lateralized processing of the verbal cues. Alternatively, they may imply that the neural mechanisms underlying shifts in internal attention to VWM representations are domain dependent. More generally our findings indicate that hemispheric asymmetry in occipital alpha is not essential for the retro-cue benefit, pointing to other possible neural mechanisms or pathways. Our findings contribute to a broader understanding of the interplay between internal attention and VWM as well as their research.